Structural and functional characterisation of human RNA helicase DHX8 provides insights into the mechanism of RNA-stimulated ADP release. Issue 18 (14th September 2019) - Felisberto-Rodrigues, Catarina; Thomas, Jemima C.; McAndrew, Craig; Le Bihan, Yann-Vaï; Burke, Rosemary; Workman, Paul; van Montfort, Rob L. M.
Abstract : DHX8 is a crucial DEAH-box RNA helicase involved in splicing and required for the release of mature mRNA from the spliceosome. Here, we report the biochemical characterisation of full-length human DHX8 and the catalytically active helicase core DHX8Δ547, alongside crystal structures of DHX8Δ547 bound to ADP and a structure of DHX8Δ547 bound to poly(A)6 single-strand RNA. Our results reveal that DHX8 has an in vitro binding preference for adenine-rich RNA and that RNA binding triggers the release of ADP through significant conformational flexibility in the conserved DEAH-, P-loop and hook-turn motifs. We demonstrate the importance of R620 and both the hook-turn and hook-loop regions for DHX8 helicase activity and propose that the hook-turn acts as a gatekeeper to regulate the directional movement of the 3′ end of RNA through the RNA-binding channel. This study provides an in-depth understanding of the activity of DHX8 and contributes insights into the RNA-unwinding mechanisms of the DEAH-box helicase family.